Expression of BRCA1 mRNA in cancerous and non-cancerous breast tissue of Bangladeshi females attending a tertiary care hospital (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Background: Dysfunctions of the BRCA1 (BReast CAncer gene1) gene are reported in cancerous and non-cancerous breast lesions. BRCA1 mRNA expression is variable in breast cancer, while this information is still inadequate in non-cancerous breast disorders. This study aimed to measure BRCA1 mRNA expression in cancerous and non-cancerous breast tissue of Bangladeshi females.Methods: The cross-sectional study was conducted on 50 breast cancer and 19 non-cancerous females. RNA was extracted from formalin-fixed paraffin-embedded breast tissue. Real-time RT-PCR was done for measuring BRCA1 mRNA. BRCA1 mRNA expressions in cancerous and non-cancerous breast tissue were compared and analysed.Results: BRCA1 mRNA expression was reduced or absent in most of the cancerous and non-cancerous (consisting of fibroadenoma, fibrocystic disease, ductal hyperplasia and normal breast tissue) breast tissue. Expression of BRCA1 in breast cancer and fibroadenoma was almost similar statistically. All cancers were invasive ductal carcinoma and of grade II, and most of them were sporadic (86%). BRCA1 expression was not associated with reproductive or cancer-related characteristics except consanguinity of marriage. The non-cancerous females were younger than the cancer patients (33.5 versus 43 years, respectively).Conclusion: The study suggests the necessity of bringing fibroadenoma patients, in addition to breast cancer patients, into the screening programme and analysing the molecular profile because their BRCA1 expression is similar.